Legal Drafting: Optimalisasi Hukum Melalui Artificial Intelligence (AI) di Indonesia - Muhana, Ahmad Fauzi (PT. Kaka Media Visi Sistematis, 2025)
The flow of technological progressivity, especially Artificial Intelligence (AI), presents a significant transformation in the Indonesian legal world, especially in legal drafting. This research aims to analyze the potential of AI in escalating the efficiency and effectiveness of legal document drafting, as well as identifying the challenges and implications for the legal profession. The research method used is a normative with a comprehensive literature study approach, utilizing secondary data from scientific journals and online sources that are aligned with the subject of this research. The main findings of this research suggest that the implementation of AI has the potential to accelerate legal drafting sequences, escalate accuracy, automate repetitive tasks, and minimize errors. However, this research also presents a series of challenges to the implementation of AI, such as the absence of clear regulatory guidance, potential bias in AI algorithms, and cyber security risks. In addition, AI implementation may displace certain routine jobs while creating the need for new skills for legal experts.